Lipidomics revealed the suppression of 5-PAHSA from human milk on macrophage foam cell formation - Zhang, Yu; Zhu, Shuang; He, Yuan; Lei, Jing Nan; Wang, Hailong; Tan, Chinping; Liu, Yuan Fa; Chen, Mingquan; Xu, Yong Jiang (American Chemical Society, 2025)
Human milk contains bioactive lipids that provide long-term cardiovascular benefits, but the specific components and mechanisms remain unclear. This study aimed to identify lactation stage-specific lipid changes and assess the role of 5-palmitic acid ester of hydroxystearic acid (5-PAHSA) in macrophage foam cell formation. Nontargeted lipidomics across colostrum, transitional, and mature milk identified 189 significantly modulated lipids, with 5-PAHSA being 1.74-fold higher in colostrum than in mature milk (p < 0.0001). In an oxidized low-density lipoprotein-induced foam cell model, 5-PAHSA reduced intracellular lipid accumulation, decreased the cholesterol ester/total cholesterol ratio by 25% (p < 0.01), upregulated cholesterol efflux/hydrolysis genes (ABCA1, ABCG1, nCEH), and downregulated uptake/esterification genes (CD36, SRA, ACAT1). Moreover, 5-PAHSA enhanced autophagic flux, possibly via the FoxO1/TFEB pathway, thereby suppressing macrophage foam cell formation. This study provides novel insights into lipid components and cardiovascular bioactivity of human milk throughout lactation.